Transforming phosphorus use on the island of Ireland: A model for a sustainable system - Macintosh, Katrina A.; Chin, Jason; Jacobs, Brent; Cordell, Dana; McDowell, Richard W.; Butler, Paul; Haygarth, Philip M.; Williams, Paul; Quinn, John P.; O'Flaherty, Vincent; McGrath, John W. (The Science of the total environment, 2019)
Phosphorus is an essential part of the world food web and a non-substitutable nutrient in all biological systems. Losses of phosphorus occur along the food-supply chain and cause environmental degradation and eutrophication. A key global challenge is to meet rising worldwide food demand while protecting water and environmental quality, and seeking to manage uncertainty around potential future phosphorus price or supply shocks. This paper presents a stakeholder-generated conceptual model of potential transformative change for implementing phosphorus sustainability on the island of Ireland via an ‘All-Island Phosphorus Sustainability’ workshop. Key transition pathways identified by stakeholders included: incentivising phosphorus recovery, developing collaborative networks to facilitate change, developing markets and value chains for recovered products; implementing data-informed practices on-farm to prevent losses and increase efficiencies, and harmonisation of technologies with end-user needs. A comparable model was previously produced for the North American region. We describe consensus and differences around key priorities between the two regions' conceptual models, and assess how the model produced for the island of Ireland can effect system-wide change and policy moving forward. Many of the transitional pathways and future aspirations presented in both models resonate globally and are highly pertinent to other jurisdictions. [Display omitted] •Stakeholder-led transformative change model for phosphorus sustainability•Perspectives from agriculture, industry, wastewater and food security•System-wide change towards phosphorus sustainability on the island of Ireland•Contrasts the island of Ireland model with a comparable model for North America•Transition pathways presented by both conceptual models resonate globally